Endobenthic Ecosystem Engineering: influence of sandprawns (Callichirus kraussi) on zooplankton assemblages - Oyatoye, Abioye E (Department of Biological Sciences, 2023)
Ecosystem engineering activities of the burrowing Southern Africa sandprawn (Callichirus kraussi), were shown in recent research to influence bentho-pelagic coupling in soft sediment estuarine ecosystems through reducing phytoplankton biomass in the overlaying water. The phytoplankton reduction mechanism was hypothesized to be driven by their adsorption along sandprawn burrow walls during irrigation. However, given that phytoplankton is a major trophic resource for filter feeders, any effect of sandprawns in reducing phytoplankton biomass may generate possible indirect effects on filter feeders such as zooplankton assemblages. To date, there has been no known research addressing questions on density of sandprawns and associated effects on zooplankton assemblages. This study therefore aimed to address this knowledge gap and quantify the influence of ecosystem engineering by C. kraussi on two size categories of zooplankton assemblages; mesozooplankton and microzooplankton, based on the premise that water pumping activities would lead to a decline in abundance of phytoplankton (adsorption onto burrow walls), thereby, resulting in negative bottom-up effects on zooplankton assemblages. This aim was accomplished using an 18-days mesocosms laboratory experiment, with each experimental mesocosm being each half-filled with sediment and water collected from the Zandvlei Estuary and divided into 3 treatments of varying C. kraussi densities (0% (control), 50% and 100% natural sandprawn density, n = 3). At the end of the experiment, increases in C. kraussi densities from controls to 100% treatments resulted in declines in abundance of total phytoplankton cells, nanophytoplankton, and picophytoplankton. However, sandprawn density had no significant effect on zooplankton assemblages, which were dominated by hyperbenthic taxa. There were discernible trends in dominance at the taxon level in microzooplankton and mesozooplankton assemblages. The copepod order Hapacticoida became increasingly dominant in both assemblages from control to 100% treatment with percentage contributions increasing from 79.23% to 95.93% in the microzooplankton assemblage and 43.07% to 92.28% in the mesozooplankton assemblage. Increasing dominance in both microzooplankton and mesozooplankton assemblages with increasing sandprawn density were confirmed using dominance plots. In conclusion, the main findings in this experiment suggest that endobenthic ecosystem engineering effects may not be confined to the sedimentary components of estuarine ecosystems but may extend to generate subtle effects on zooplankton taxa, mainly by way of increasing dominance. This study is the first direct evidence of the bentho-pelagic coupling effects of endobenthic ecosystem engineers on pelagic zooplankton assemblages that are dominated by hyperbenthic taxa and lays the foundation for subsequent research into understanding consequences of endobenthic ecosystem engineering on pelagic ecosystems.